2018
DOI: 10.21577/0100-4042.20170176
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Approaches to Study Learning in the Tertiary Level Chemistry Laboratory

Abstract: Despite the widespread notion amongst chemistry educators that the laboratory is essential to learn chemistry, it is often a neglected area of teaching and, arguably, of educational research. Research has typically focused on secondary education, single institutions, and isolated interventions that are mostly assessed quantitatively. It has also honed in on compartmentalised features instead of searching understanding of broader aspects of learning through experimentation. This paper contends there is a gap in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(51 reference statements)
0
8
0
2
Order By: Relevance
“…Articles about the role of laboratory, its purpose and effectiveness to obtain learning outcomes of chemistry education are noteworthy [1,25,26,27]. Despite the widespread notion amongst chemistry educators that the laboratory is essential location to learn chemistry, it is often a neglected area of teaching and, arguably, of educational research [27]. Researchers state that learning of chemistry in experimental laboratory environments should be made more effective [1,25].…”
Section: Discussionmentioning
confidence: 99%
“…Articles about the role of laboratory, its purpose and effectiveness to obtain learning outcomes of chemistry education are noteworthy [1,25,26,27]. Despite the widespread notion amongst chemistry educators that the laboratory is essential location to learn chemistry, it is often a neglected area of teaching and, arguably, of educational research [27]. Researchers state that learning of chemistry in experimental laboratory environments should be made more effective [1,25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for this cohort of teachers physics would be learned more through teaching (preparing and reviewing) than by earning additional academic degrees. This speaks of the different natures of the three sciences and of the particularities associated with learning and teaching each subject, for instance the level of abstraction necessary to master each of them (Bucat, 2004;Sandi-Urena, 2018) . In addition, data indicated that private university training is associated with less mastery of the subject, especially in physics.…”
Section: Discussionmentioning
confidence: 99%
“…Sandi‐Urena (2018) suggested the use of naturalistic approaches to investigate students’ learning with the goal to “uncover the internal and invariant structure of a chosen phenomenon not in its empirical individuality but in its essence” (p. 238). The author then goes on to defend the use of such approaches, stating:
Unlike experimental approaches, naturalistic ones start off without hypotheses or theories to be falsified.
…”
Section: Methodsmentioning
confidence: 99%
“…… gaining a realistic perspective and understanding of learning in the laboratory is plausible. (p. 238).Given the importance and utility of investigating students’ perceptions of their experiences in the chemistry laboratory (Sandi‐Urena, 2018), this study focuses on students’ perceptions around creativity and critical thinking in the chemistry laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation